VERTICAL DISTRIBUTION OF NUTRIENTS IN GROUNDNUT GROWING SOILS IN SEMIARID REGION OF VARATHURU WATERSHED IN CHITTOOR DISTRICT - G.P. LEELAVATHY, M.V.S. NAIDU*, T. GIRIDHARA KRISHNA, K.V. RAMANA, V. CHANDRIKA; P. SUDHAKAR (The Journal of Research ANGRAU, 2021)
The land survey was undertaken to study the vertical distribution of plant nutrients in the soil profiles/ pedons in groundnut growing areas of Varathuru watershed in Chittoor district to understand nutrient supply capacity of soils. The results revealed that plant available P and K in these soils were sufficient in the surface and subsurface horizons of all pedons except pedon 2 , wherein, P was deficient in the subsurface horizon. Exchangeable Ca and Mg and available S were sufficient in surface and subsurface soils of all pedons except pedon 3 wherein S was deficient in surface horizon. The available S and exchangeable Ca and Mg in pedons 1 and 4 were high in surface horizons than in subsurface horizons and pedons 2, 3 and 5 showed an inconsistent trend with depth. The DTPAextractable Cu and Mn in these soils were found to be above critical limits in surface and subsurface horizons in all the pedons except in pedons 1 and 5 for Cu in subsurface horizons and Mn in surface horizon in pedon 4. The available Zn was deficient in all the pedons except pedons 2 and 5 in surface horizons and the available Fe was found to be above critical limits in surface horizons in all the pedons and below critical limit in subsurface horizons in pedons 2 and 4. All the micronutrients were higher in surface soils than for subsurface soils except in pedon 5 for Zn and Cu, pedons 1 and 5 for Fe and pedon 3 for Mn.